Case report: Prader-Willi syndrome and inflammatory arthritis-An important consideration - Luca Marelli; Tomáš Dallos; Elisabetta Miserocchi; Elisabetta Miserocchi; Paolo Nucci; Beatrice Tombolini; Beatrice Tombolini; Orazio De Lucia; Maurizio Gattinara; Roberto Caporali; Roberto Caporali; Roberto Caporali; et al. (Frontiers Media S.A., 2023)
BackgroundPrader-Willi syndrome (PWS) is a multisystemic genetically determined disorder. Musculoskeletal manifestations are common in most patients. We report the cases of two children with PWS who developed inflammatory arthritis, complicated with chronic anterior bilateral uveitis in one case. To our knowledge, no previous reports of such an association exist.Case presentationCase 1 was of a 3-year-old girl diagnosed with PWS who developed arthritis of the right knee with morning stiffness, joint swelling, and limited range of motion. Other causes of arthritis were ruled out. Increased inflammatory markers, antinuclear antibody (ANA) positivity, and hypertrophic synovitis on ultrasound confirmed the diagnosis of inflammatory arthritis compatible with juvenile idiopathic arthritis (JIA). Despite the treatment with methotrexate, arthritis progressed, and etanercept was added. The patient reached and maintained articular remission while on combined MTX and etanercept treatment during 9 years of follow-up. Case 2 was of a 6-year-old boy diagnosed with PWS who developed arthritis of the right knee. Laboratory investigations showed mildly increased acute phase reactants, microcytic anemia, and ANA positivity at high titer (titer 1:1,280). Infectious and other causes of arthritis were excluded. Ultrasound confirmed the presence of joint effusion and synovial thickening, and synovial fluid analysis was consistent with inflammatory arthrosynovitis (white blood cell count of 14,200/µl) compatible with JIA. Shortly after the diagnosis, the ophthalmologic evaluation revealed the presence of bilateral anterior uveitis. Despite MTX and topical corticosteroid, ocular inflammation persisted and adalimumab was added. At the last follow-up, 9 months later, the child experienced inactivity of arthritis and uveitis with normal growth.ConclusionsWe aim to raise awareness of this possible association among pediatricians since arthritis might be underestimated due to high pain tolerance, behavioral disturbances, and other musculoskeletal abnormalities in PWS patients.